PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN KSP KARYA HARTA JAYA - Rahadiyan Rahadiyan; Ida Bagus Alit Ksama Putra; Kunto Ajibroto; Leni Herfiyanti; Putri Dwi Novrina; I Putu Ajie Windu Kertayoga (Jurnal Ilmiah Magister Ilmu Administrasi, 2023)
This study aims to examine the effect of: (1) organizational culture and motivation on employee performance, (2) organizational culture on employee performance, (3) motivation on employee performance. The research design used in this research is causal quantitative research. In this study, the research subjects were employees who worked at KSP Karya Harta Jaya and the objects of research were organizational culture, motivation and employee performance. The population taken in this study is all employees who work at KSP Karya Harta Jaya which amounts to 25 employees. Data were collected by interviews, document recording and questionnaire methods, then analyzed by multiple regression analysis. The results showed that: (1) organizational culture and motivation have a significant effect on employee performance, (2) organizational culture has a significant effect on employee performance, (3) motivation has a significant effect on employee performance.